Membangun Jembatan Literasi: Pendampingan Kesadaran Membaca Melalui Teknik Read Aloud Pada Masyarakat Pesisir Tanjung Pasir, Kota Tarakan - Wahyuni, Erna; Thobroni, Muhammad; Hanna Fauziyyah, Nurul; Cahyono Aji, Dwi; Ilham, Muhammad Ilham; Ani Wijiati, Iva; Riyanti, Asih; Setyami, Inung; Armansa, Ade; Fatonah, Siti; Kumala Sari, Rita (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Low literacy awareness in coastal communities is a structural problem that impacts children's language and cognitive development from an early age. The coastal community of Tanjung Pasir, Tarakan City, faces limited access to reading materials, minimal family reading practices, and low parental involvement in children's literacy activities. This community service activity aims to build reading awareness through contextual, participatory, and coastal environmental-based read-aloud techniques. The implementation method consists of four stages: (1) survey and coordination with the community; (2) community service team discussions to prepare materials and activity tools; (3) implementation of the mentoring activities; and (4) reflection and evaluation of the activities. The results of the activity indicate an increased understanding of parents about the importance of reading aloud, more expressive read-aloud practice skills, and a growing awareness that reading can be done using simple learning resources in the local environment. This program contributes to building a family literacy bridge and fostering an early literacy ecosystem in coastal areas.